2022
DOI: 10.1038/s41591-022-01768-5
|View full text |Cite
|
Sign up to set email alerts
|

Swarm learning for decentralized artificial intelligence in cancer histopathology

Abstract: Artificial intelligence (AI) can predict the presence of molecular alterations directly from routine histopathology slides. However, training robust AI systems requires large datasets for which data collection faces practical, ethical and legal obstacles. These obstacles could be overcome with swarm learning (SL), in which partners jointly train AI models while avoiding data transfer and monopolistic data governance. Here, we demonstrate the successful use of SL in large, multicentric datasets of gigapixel his… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 121 publications
(58 citation statements)
references
References 51 publications
0
58
0
Order By: Relevance
“…A key limitation is that many clinically relevant genes were not analyzable due to having fewer than 25 mutants in TCGA. Large-scale efforts are needed to create datasets with a sufficient size, which could be facilitated by federated 22 or swarm 23 learning. Since the early 2000s, studies have shown a link between genetic alterations and histological phenotypes 24 , which DL can exploit.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…A key limitation is that many clinically relevant genes were not analyzable due to having fewer than 25 mutants in TCGA. Large-scale efforts are needed to create datasets with a sufficient size, which could be facilitated by federated 22 or swarm 23 learning. Since the early 2000s, studies have shown a link between genetic alterations and histological phenotypes 24 , which DL can exploit.…”
Section: Main Textmentioning
confidence: 99%
“…A key limitation is that many clinically relevant genes were not analyzable due to having fewer than 25 mutants in TCGA. Large-scale efforts are needed to create datasets with a sufficient size, which could be facilitated by federated 22 or swarm 23 learning.…”
Section: Main Textmentioning
confidence: 99%
“… 9 When training multicentric models on medical data, SL has its advantages over FL, because it centralizes neither the data nor the models ( Figure 1 ). Prior to the recent study by Saldanha et al., 10 there was no application of SL to cancer histopathology data, making the study a pioneer in the field of computational histopathology.
Figure 1 Different model training strategies Conventional merged data training involves data sharing and aggregation (left).
…”
Section: Main Textmentioning
confidence: 99%
“…In the last five years, decentralized machine learning approaches have been proposed which could alleviate the need for physical data exchange. The most prominent examples include federated learning (FL) and swarm learning (SL) [15][16][17]. In these approaches, multiple datasets are located on physically separate computers, with the DL model trained on each computer separately [16].…”
Section: Introductionmentioning
confidence: 99%